(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Bryophytes are important in traditional medicine, and about 150 ethnobotanical species are recognized worldwide. This article lists 20 medicinal bryophytes that are part of the bryoflora of Uzbekistan and are used in traditional medicine of the peoples of the world.